Monitoring of the corrosion behaviour of the reinforcement at a cooling tower working in sea water operation using embeddable polymeric cathode sensors - Raupach Michael; Helm Christian; Eisenkrein-Kreksch Helena (MATEC Web of Conferences)
Continuous monitoring of the effectiveness of repair measures carried out in connection with chloride-induced corrosion of the reinforcement is often only possible when using sensor-based monitoring systems. The targeted integration of sensors in existing structures represents a technical difficulty. For this purpose, special corrosion sensors based on the supplementary cathode principle have been developed and tested on a laboratory scale at the Institute for Building Materials Research (ibac) at RWTH Aachen University. For this purpose, a special polymer has been developed at ibac allowing the embedment of the sensors and a suitable electrical connection between sensors and the surrounding concrete. Laboratory tests have been carried out to show the general functioning of the system and to optimize the performance. The first practical application of the measuring system will be described and explained in the presentation: The corrosion condition of the reinforcement on the outside of a cooling tower in seawater operation is monitored at selected points following an extensive repair measure. The results of the first measurements on site will be shown and discussed. The theoretical background, the first project and the experiences from the installation and commissioning of the monitoring system under the challenging local conditions will be presented.